Peranan Probiotik Lactobacillus plantarum IIA-1A5 dalam Meningkatkan Ketahanan Tubuh, Performa, dan Kualitas Telur Ayam Komersial - Yodilla Agpretasia; Niken Ulupi; Irma Isnafia Arief (Jurnal Ilmu Pertanian Indonesia, 2024)
Probiotics are microorganisms that are non-pathogenic and beneficial for health when used in certain doses through the mechanism of increasing the function of the small intestine in chickens. This study aims to analyze the effect of adding the probiotic Lactobacillus plantarum IIA-1A5 to feed to improve the body's immune system, production performance, and egg quality in laying hens aged 49‒52 weeks. The experimental design used was a Completely Randomized Design (CRD). The treatment for adding the probiotic Lactobacillus plantarum IIA-1A5 to feed consists of four treatment levels, namely P0 (without probiotics), P1 (feed + 8.1 x 106 cfu/g or 1 g/kg feed), P2 (feed + 2.43 x 107 cfu/g or 3 g/kg feed), and P3 (feed + 4.86 x 107 cfu/g or 6 g/kg feed). The results of the study showed that administering the probiotic Lactobacillus plantarum IIA-1A5 in feed could reduce Escherichia coli bacteria in the small intestine of laying hens. Giving the probiotic Lactobacillus plantarum also had a significant effect (P<0.05) on feed consumption and egg yolk color. The addition of the probiotic Lactobacillus plantarum IIA-1A5 in feed can increase animal resistance, performance, and quality of chicken eggs. The use of probiotics with a treatment level of 1 g kg-1 feed (8.1 x 106 cfu g-1) showed the best results. Keywords: heat stress, laying hens, probiotic